Super-resolution imaging reveals the evolution of higher-order chromatin folding in early carcinogenesis - Jianquan Xu (Nature Portfolio, 2020)
Aberrant chromatin structure is often found in cancer. Here, the authors optimise super-resolution microscopy for pathological tissue and discovered a significant decompaction of chromatin folding in early carcinogenesis prior to tumour formation.